Effects of Sub-Occipital Muscles Inhibition Technique and Cranio-Cervical Flexion Exercise for Mechanical Neck Pain - Robina Malik, Kinza Anwar, Hafsah Arshad, Nida Mushtaq Kayani, Ammara Malik, Shazana Khalid, Lal Gul Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To compare the effects of Suboccipital muscle Release (SMI) techniques and Cranio-Cervical Flexion Exercise (CCFE) for Range of motion, pain, neck disability and forward head posture (FHP) in mechanical neck pain patients. Methodology: This Randomize Clinical Trial was conducted in Railway General Hospital Rawalpindi, within a duration of 6 months.Total 28 patients who fullfilled inclusion criteria such as were randomly allocated equall into two treatment groupthrough lottery method. Group A received suboccipital muscle inhibition technique while Group B received craniocerviacal flexion exercises. Both groups were evaluated at baseline and after four weeks through numeric pain rating scale (NPRS), Neck Disability Index (NDI), Goniometer, and craniovertebral angle. IBM SPSS 24 was used for statistical analysis.Parametric test i.e., independent t test was applied on normal distributed data for between group analysis and Paired t test was applied for within group analysis for NDI. Non-parametric test i.e., Mann- Whitney U test was applied for between group analysis and Wilcoxon test were applied for within group analysis for FHP, NPRS and ROM. Results: Groups A and Group B showed significant improvement (p˂0.05) in within group analysis in Numeric Pain Rating Scale, forward head posture, neck disability index and cervical range of motion. Practical implication: Mechanical neck pain accounts approximately 50% to neck pain and may induce functional disability in many patients. The current study findings can be used to formulate effective, accessible andeconomical treatment strategies for Mechanical neck pain, so it may be interesting to the readers ofyour journal. Conclusion: Sub occipital muscle inhibition technique and cranio cervical flexion exercises areequally effective techniques to increase cervical range of motion, decrease neck disability, decrease pain intensity, and improvecranio-vertebral angle in patients with mechanical neck pain. Keywords: Cranio-cervical flexion exercises, Cranio-vertebral angle, Neck Disability Index, Range of Motion,